Analisis Perjanjian dalam Mencapai Kepastian Hukum Berbasis Nilai Keadilan - Dwi Atmoko; Lindri Purbowati (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
With the contract agreement, it is expected that each individual will keep their promises and carry them out. The concept and meaning of justice as the purpose of making an agreement used in this paper is to emphasize the role of aspects of contract justice values ​​and the elements contained in the law of agreements. This provision gives the parties the freedom to make agreements as long as they do not conflict with the law, public order and morality. Thus, the parties are given the opportunity to make clauses that vary from the provisions of Book III of the Civil Code. Provisions that can be set aside are optional or optional, while provisions that are mandatory such as the requirements for the validity of the agreement are provisions that cannot be set aside by the parties. Thus, from the review, the parties who wish to bind themselves into a legal relationship in a contract certainly need to have a good understanding of all aspects of the implementation of contracts in business activities so that in the future it does not cause undesirable consequences. An agreement is a legal document that regulates the rights and obligations of the parties who make it. If there is a dispute regarding the implementation of the agreement between the parties, the document will be referred to for resolution of the dispute. If a dispute cannot be resolved easily through negotiations between the parties themselves because it takes a lot of time and energy, they will resolve it through a litigation process in court, where the contents of the agreement will be used as the basis for the judge to resolve the dispute.